Autonomous Delivery Vehicles: A Quantitative Study from the Perspective of Innovativeness - Yildiz, Bülent (Istanbul University, 2024)
E-commerce has become increasingly popular, making the effective management of timely and accurate deliveries critical to maintaining customer satisfaction. Autonomous delivery vehicles (ADVs) are recent innovations essential to the distribution sector. However, their popularity depends on how open consumers are to innovations. Therefore, this study addressed whether consumers’ innovativeness affected their perceived usefulness and risks associated with ADVs. The study also investigated whether consumers who were more open to innovations were more willing to use ADVs. The sample consisted of 184 participants from different cities of Türkiye and data were collected using several analyses. The results showed that participants who believed in the usefulness of ADVs were more likely to use them whereas participants who focused more on the risks were less likely. Innovativeness did not affect how participants perceived the risks of ADVs.
Keywords: autonomous delivery vehicles; Innovativeness; Autonomous Delivery Vehicles; Structural Equation Modeling; innovativeness; Yöneylem; structural equation modeling; Transportation and communications; Operation; HE1-9990; 11. Sustainability; 16. Peace & justice